Convective heat transfer of laminar nano-fluids flow through a rectangular micro-channel with different types of baffle-corrugation. Issue 1 (2nd January 2022) - Saha, Sandip; Biswas, Pankaj; Raut, Santanu; Das, Apurba Narayan
Abstract: Under uniform heat flux, a detailed numerical study has been performed to investigate the thermophysical properties of the laminar nano-fluids flow through a baffle-corrugation (plane, trapezoidal, isosceles, and half-circular) rectangular micro-channel with the variations of Reynolds number, baffles aspect ratio, different kind of base fluids, nano-particles, and diameter of nano-particles. The Finite volume method has been employed to solve the governing equations and the Fluent software has been used to depict the simulations. From the present study, it is found that the half-circular baffle-corrugation provides the highest Nusselt number among all the baffle-corrugation shapes.